RELIABILITAS DAN FEASIBILITAS PENGGUNAAN KARTU MENUJU SEHAT PERKEMBANGAN (KMS-P) MOTOR MILESTONE ANAK UMUR 3-18 BULAN DI PUSKESMAS DAN POSYANDU - Yayah K. Husaini; Abas B. Jahari; Heryudarini Harahap; Yekti Widodo; Fawzia A. Hadis (Persagi, 2006)
RELIABILITAS DAN FEASIBILITAS PENGGUNAAN KARTU MENUJU SEHAT PERKEMBANGAN (KMS-P) MOTOR MILESTONE ANAK UMUR 3-18 BULAN DI PUSKESMAS DAN POSYANDU.Background: To monitor growth and development of a child could use the Road to the Health Card of Under Five (KMS-Balita) for growth and Road to the Health Card of Motor Development (KMS-Perkembangan) for development. The KMS-Perkembangan (KMS-P) has been developed based on a scientific research design following the WHO-procedure for the development of a reference. In order the KMS-P could be used at Posyandu and/or at Puskesmas, it needs to be examined the reability and the feasibility in the field condition.Objectives: To examine the reliability and the feasibility of using KMS-P for children aged 3-18 months underfield condition.Methods: The study was carried out in Bogor City and Sukabumi District A total of 10 Puskesmas and 74 Pusyandu located in 19 villages were included as the study sites. The crossectional study designed was implemented, and 872 mothers and their children aged 3-18 months, 75 village cadres and 37 health providers were included as the sample studied. Data on general characteristics and motor milestones, reability and feasibility of using the KMS-P included plotting, its interpretation, and evaluating the child motor development were collected.Results: The study reveals that under field condition, 100% of health providers, 74.7% of village cadres and 77.56% mothers of the children studied could use the KMS-P property. The KMS-P has been developed simple, practicable, and action oriented.Conclusions: The reliability and feasilility of using KMS-P under field condition is highly acceptable. The prospect of KMS-P is very encouraging.Keywords: reliability, feasibility, motor milestone, motor development.